Protective and therapeutic effect of Vitex agnus-castus against prostate cancer in rat - Abeer Y. Ibrahim, Samah A. El-Newary, Eman R. Youness, Amr M.M. Ibrahim, Walaa A. El Kashak (Journal of Applied Pharmaceutical Science, 2017)
This work was prompted to investigate effect of the vitex berries crude extract on prostate cancer relevant to the cancer growth rate limiting enzymes (5-α reductase and Na+/K+ ATPase, tumor biomarker; prostate specific antigen (PSA), carcinoembryonic antigen (CEA), sexual hormones; testosterone and luteinizing hormone, anti-inflammatory markers and antioxidant markers. Vitex berries crude extract was prepared and tested against human prostate cancer cell line (PC3) and then incorporated into in-vivo model for prostate cancer induced chemically in rats using chronic administration of testosterone (3mg/ kg/ 90 days) in a sub-cutaneous route and intraperitoneal injection of carcinogenic material, 7,12-Dimethylbenz(a)anthracene (DMBA) at dose of 65 mg/kg as a single dose. Vitex extract at dose of 165 mg/kg/day inhibited cell growth of PC3 which were completely killed at 100μg/ml. In in-vivo study, Vitex extract showed potent anti-prostate cancer evident as significant reduction in cancer growth rate limiting enzymes; 5-α reductase, Na+/K+ ATPase and prostate specific antigen with suppression in carcinoembryonic antigen production, which amplified by prostate cancer induction. A selective anti-inflammatory effect was recorded with vitex administration represented as significant inhibition in cyclooxygenase-2 and non-significant effect on cyclooxygenase-1. It showed ameliorative effects on sexual hormones showed in amendment in testosterone and luteinizing hormone affected by prostate cancer induction. Investigations of this work prove vitex extract has potential role as anti-prostate cancer evaluated by in-vitro and in-vivo protocols. The anti-prostate cancer properties of vitex extract may be due to its effect against cancer risk factors; antioxidant and anti-inflammatory characters, ameliorative effect on sex hormones and suppression in cancer growth rate limiting enzymes.
Keywords: Prostate cancer, vitex, antiandrogen,Na+/K+ ATPase inhibitors, 5-É ‘ reductase, 7,12-Dimethylbenz(a)anthracene.